2021
DOI: 10.7759/cureus.15788
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends of Carcinoma: Experience of a Tertiary Care Cancer Center in North India

Abstract: Cancer incidence across the geographical area is mercurial and factors like dietary habits, environment, social structure, genetics govern relative incidence. Malwa region of Punjab is one such geographical area of India speculated to have a higher incidence of cancer. The current analysis was done to assess the occurrence of cancer in the region and to analyze the trends and types of carcinoma with age, gender, site, and histopathological type, and to compare with the trends mentioned in the literature. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Distinctively, ESCC represents 90%, while AC represents 10% of total EC cases worldwide ( 4 ). In line with this, our previous hospital-based study demonstrated 96.5% of esophagus tumors were squamous cell carcinoma, whereas 1.7% were adenocarcinoma ( 2 ). Despite the higher percentage of ESCC, its etiology remains poorly understood due to its heterogeneous nature.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Distinctively, ESCC represents 90%, while AC represents 10% of total EC cases worldwide ( 4 ). In line with this, our previous hospital-based study demonstrated 96.5% of esophagus tumors were squamous cell carcinoma, whereas 1.7% were adenocarcinoma ( 2 ). Despite the higher percentage of ESCC, its etiology remains poorly understood due to its heterogeneous nature.…”
Section: Introductionsupporting
confidence: 70%
“…As per the recent GLOBOCAN 2020 data, esophageal cancer (EC) is the eighth most common cancer and the sixth leading cause of death globally ( 1 ). Moreover, a hospital-based analysis of 2088 patients in Northern India revealed esophageal cancer as the fourth (10.39%) most prevalent cancer ( 2 ). Because of the substantial increase in the incidence and mortality rates along with the decrease in the 5-year survival rate of EC (~18%), esophageal cancer has become a severe global public health challenge ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In males most common age group was 50-60 years while in females 40 to 50 year. The study conducted by Rana., et al[18] shown 51-60 year of age in females most common age group and 61-70 years was commonest amongst male study done by Bal., et al[19] shown 50-54 years was the commonest age group amongst females and 65-69 years amongst males. In our study 54% were females and 46% males.…”
mentioning
confidence: 93%
“…Endometrial carcinoma (EC) is the most common gynecological cancer with a global incidence of 23.2 per 1 lakh population (1)(2)(3). In India, the EC accounts for 11.50% of female genital tract cancers, which is next to cervical and ovarian cancer (4). Bokhman identified two distinct forms (types I and II) of EC.…”
Section: Introductionmentioning
confidence: 99%